The Global Multi-Country Model (GM): an Estimated DSGE Model for the Euro Area Countries - Alice Albonico; Ludovic Calès; Roberta Cardani; Olga Croitorov; Filippo Ferroni; Massimo Giovannini; Stefan Hohberger; Beatrice Pataracchia; Filippo Pericoli; Rafal Raciborski; Marco Ratto; Werner Roeger; et al. (Publications Office of the European Union, 2017)
This paper presents the European Commission's Global Multi-country model (the GM model). The GM model is an estimated multi-country DSGE model, developed by the European Commission, that can be used for spillover analysis, forecasting and medium term projections. Its development is jointly performed by the Joint Research Centre and DG ECFIN. Since the GM model is developed to be flexible under different country configurations,we present the GM model in its configuration designed for EMU-countries (GM3-EMU), which has been estimated for the four largest European economies (Germany, France, Italy and Spain). We analyse business cycle properties, present the model fit and provide a quantitative assessment of the relative importance that supply, demand and international shocks as well as discretionary policy interventions had in explaining the cyclical patterns observed in each country since the establishment of the EMU.
Keywords: C51; E31; 330; DSGE; Bayesian estimation; EMU; Business cycle; Model fit; Cross-country comparison